2002
DOI: 10.1590/s0102-05362002000200016
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade, acúmulo de nitrato e estado nutricional de cultivares de alface, em hidroponia, em função de fontes de nutrientes

Abstract: A alface é a hortaliça folhosa mais comercializada no Brasil, é boa fonte de vitaminas e sais minerais, destacando-se seu elevado teor de vitamina A. É adaptada a clima ameno, sendo própria para cultivo no inverno quando atinge as maiores produções. A limitação do cultivo no verão é a baixa qualidade do produto que eleva o preço nesse período (Delistoianov, 1997 UFV, Depto. Fitotecnia, Para o cultivo hidropônico, têm sido encontradas boas alternativas comerciais, mesmo em mercados tradicionais, como as CEASAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
37

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 9 publications
3
7
0
37
Order By: Relevance
“…These values are about 50% of the maximum value of 1,700 mg kg -1 fresh weight observed in the lettuce cvs. Grandes Lagos, Regina, and Baba de Verão, in an experiment conducted during the autumn in Viçosa, Minas Gerais state, Brazil (Fernandes et al, 2002) and similar to those observed in nutrient solution with 100 mg L -1 of N-NO 3 -for the lettuce cvs. Brisa, Divina, and Prima, of 940.0, 844.5, and 719.8, respectively (Lastra et al, 2009).…”
Section: Resultssupporting
confidence: 76%
“…These values are about 50% of the maximum value of 1,700 mg kg -1 fresh weight observed in the lettuce cvs. Grandes Lagos, Regina, and Baba de Verão, in an experiment conducted during the autumn in Viçosa, Minas Gerais state, Brazil (Fernandes et al, 2002) and similar to those observed in nutrient solution with 100 mg L -1 of N-NO 3 -for the lettuce cvs. Brisa, Divina, and Prima, of 940.0, 844.5, and 719.8, respectively (Lastra et al, 2009).…”
Section: Resultssupporting
confidence: 76%
“…Nestes tratamentos, as concentrações encontradas na parte aérea estão dentro da faixa (4 a 6 g kg -1 ) considerada como adequada para a cultura (REUTER; ROBINSON, 1997). No entanto são inferiores aos teores estabelecidos por Fernandes et al (2002), que encontraram valores de 8,5 g kg -1 .…”
Section: Resultsunclassified
“…Diferentemente, Williams e Nelson (1997) observaram em crisânte-mo, que as plantas cultivadas em substrato com zeólita enriquecida com potássio, apresentaram maiores teores que as testemunhas que receberam fertilizantes na forma solúvel. Os resultados da concentração de potássio, nos tecidos da parte aérea, foram menores que o valor médio de 71 g kg -1 encontrado por Fernandes et al (2002) para a mesma cultivar de alface utilizada neste estudo. Também estão abaixo da faixa adequada (50 a 80 g kg -1 ) proposta por Reuter e Robinson (1997).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…The lettuce crop yield was assessed in function of nutrient sources, in hydroponic cropping, and it was concluded that there was little influence from the nutritive solution (Fernandes et al, 2002). In hydroponic cropping of lettuce with six nutritive solutions, it was concluded that the solution suggested by Castellane & Araújo (1995) presented superior production to the others and the best qualitative aspect (Santos, 2010).…”
Section: Nutrientsmentioning
confidence: 99%